Billboard advertising: an avenue for communicating healthcare information and opportunities to disadvantaged populations - James K. Elrod; John L. Fortenberry (BMC Health Services Research, 2017)
Abstract Background Healthcare communications directed toward the disadvantaged have the potential to elevate the health status of these underprivileged and highly-challenged individuals. From conveying advice which encourages healthy lifestyles to communicating the location and availability of various medical resources, healthier lives and communities can be realized. Success on this front first requires establishing an effective communications link, something that is made more difficult as communications options available to the disadvantaged are more limited than those available to advantaged populations. Discussion One avenue which shows exceptional promise for successfully engaging the disadvantaged is that of billboard advertising. Willis-Knighton Health System’s experiences and insights indicate that the characteristics and qualities of billboards, paired with the environmental circumstances typically faced by the less fortunate, create unique combinations which amplify consumption of billboard advertising content. Further, research suggests that the less privileged place greater reliance on the medium than do their more privileged counterparts, escalating the value and impact potential of billboard advertising directed toward the disadvantaged. Conclusions Given the value afforded by health and wellness information successfully reaching the disadvantaged, opportunities to better distribute content to targeted audiences could very well improve community health. Billboard advertising appears to be well suited to engage the less fortunate, providing a productive pathway for the conveyance of helpful, supportive details, yielding healthier populations, enhanced opportunities, and better communities.